Data Encryption Approach For Security - Arya, Richa (International Journal of Computer Sciences and Engineering, 2014)
Whenever any new algorithm for data encryption is designed the main concern is upon the security of data. As encryption is done for encrypt data or change data in a secure form, so such encryption techniques should be used which provide the best security to the network. The main goal of any algorithm should be to secure data from any outside attack. In the recent days there are so many security issues regarding exchanging of data through a network. So data has to be encrypted in such a way that there is no threaten to secutiry. A new approach for data encryption is provided in this paper which will be helpful for security of data.